Reverse Coefficient

Algebra Level 3

Two cubic function f ( x ) = x 3 + a x 2 + b x + c f(x)=x^3+ax^2+bx+c and g ( x ) = c x 3 + b x 2 + a x + 1 g(x)=cx^3+bx^2+ax+1 satisfy the following.

  • f ( 3 ) = 0 f(3)=0 , g ( 4 ) = 0 g(4)=0

  • The value of lim x p f ( x ) g ( x ) \displaystyle\lim_{x\rightarrow p}\frac{f(x)}{g(x)} exists for all real p 4 p\neq 4 .

What is the value of lim x 1 f ( x ) + g ( x ) x + 1 \displaystyle\lim_{x\rightarrow -1}\frac{f(x)+g(x)}{x+1} ?

7 3 4 6 5

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Sep 8, 2019

Note that g ( X ) = X 3 f ( X 1 ) g(X) = X^3f(X^{-1}) so that, for u 0 u \neq 0 , f ( u ) = 0 f(u) = 0 if and only if g ( u 1 ) = 0 g(u^{-1}) = 0 . Since g ( 3 ) = 0 g(3)=0 , f ( 1 3 ) = 0 f(\tfrac13) = 0 . Since f ( X ) g ( X ) \tfrac{f(X)}{g(X)} is well-behaved as X 3 X \to 3 , we also have f ( 3 ) = 0 f(3) = 0 . Thus f ( X ) = ( X 4 ) ( X 3 ) ( X 1 3 ) g ( X ) = 1 4 ( X 1 4 ) ( X 1 3 ) ( X 3 ) f(X) \; = \; (X - 4)(X-3)(X-\tfrac13) \hspace{2cm} g(X) = -\tfrac14(X - \tfrac14)(X - \tfrac13)(X - 3) and hence f ( X ) + g ( X ) = 3 4 ( X + 1 ) ( X 1 3 ) ( X 3 ) f ( X ) + g ( X ) X + 1 = 3 4 ( X 1 3 ) ( X 3 ) \begin{aligned} f(X) + g(X) & =\; \tfrac34(X+1)(X - \tfrac13)(X - 3) \\ \frac{f(X) + g(X)}{X + 1} & = \; \tfrac34(X - \tfrac13)(X - 3) \end{aligned} so that lim X 1 f ( X ) + g ( X ) X + 1 = 3 4 × 4 3 × 4 = 4 \lim_{X \to -1} \frac{f(X)+g(X)}{X+1} \; = \; \tfrac34 \times -\tfrac43 \times -4 \; = \; \boxed{4}

Junghwan Han
Sep 8, 2019

f ( 3 ) = 27 + 9 a + 3 b + c = 0 f(3)=27+9a+3b+c=0

g ( 4 ) = 64 a + 16 b + 4 a + 1 = 0 g(4)=64a+16b+4a+1=0

f ( 3 ) = 27 + 9 a + 3 b + c = 27 ( 1 27 c + 1 9 b + 1 3 a + 1 ) = 27 g ( 1 3 ) = 0 \displaystyle f(3)=27+9a+3b+c=27\cdot\left(\frac{1}{27}c+\frac{1}{9}b+\frac{1}{3}a+1\right)=27\cdot g\left(\frac{1}{3}\right)=0

g ( 1 3 ) = 0 \displaystyle\therefore g\left(\frac{1}{3}\right)=0

Since the value of lim x 1 3 f ( x ) g ( x ) \displaystyle\lim_{x\rightarrow\frac{1}{3}}\frac{f(x)}{g(x)} exists, f ( 1 3 ) = 0 \displaystyle f\left(\frac{1}{3}\right)=0

f ( 1 3 ) = 1 27 + 1 9 a + 1 3 b + c = 0 \displaystyle f\left(\frac{1}{3}\right)=\frac{1}{27}+\frac{1}{9}a+\frac{1}{3}b+c=0

Now, lim x 1 f ( x ) + g ( x ) x + 1 = lim x 1 ( c + 1 ) x 3 + ( a + b ) x 2 + ( a + b ) x + ( c + 1 ) x + 1 = lim x 1 ( c + 1 ) ( x + 1 ) ( x 2 x + 1 ) + ( a + b ) x ( x + 1 ) x + 1 = lim x 1 { ( c + 1 ) ( x 2 x + 1 ) + ( a + b ) x } = 3 c + 3 a b \displaystyle\lim_{x\rightarrow -1}\frac{f(x)+g(x)}{x+1}=\lim_{x\rightarrow -1}\frac{(c+1)x^3+(a+b)x^2+(a+b)x+(c+1)}{x+1}=\lim_{x\rightarrow -1}\frac{(c+1)(x+1)(x^2-x+1)+(a+b)x(x+1)}{x+1}=\lim_{x\rightarrow -1}\left\{(c+1)(x^2-x+1)+(a+b)x\right\}=3c+3-a-b

If you do the calculation, you will get the answer 4 4 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...